Characteristic and Functional Study of Intersex, a Gene Related to Female Fertility in Bemisia tabaci - Liu, Yating; Yang, Jinjian; Huo, Zhijia; Wang, Shaoli; Wu, Qingjun; Zhou, Xuguo; Xie, Wen; Zhang, Youjun (Frontiers in Physiology, 2020)
The intersex (ix) gene acts in concert with doublesex (dsx) at the end of the sex determination hierarchy to control somatic sexual differentiation in Drosophila melanogaster. Here, we report the Drosophila ix homologue in Bemisia tabaci (Btix) with differential splicing events. Four isoforms were found in B. tabaci adults, including two sex-specific transcripts (BtixF and BtixM). Knockdown of Btix had no measurable effects on female morphological phenotypes but reduced the expression of the vitellogenin gene and resulted in the production of significantly fewer eggs, a lower eclosion rate and a shorter body size of female progeny in comparison with control females. These results increase our understanding of the genes underlying sex determination in B. tabaci and reveal a potential target for RNA interference-based pest management.